Price discount framings on product bundles with shipping surcharges in the Indian market: Examining the weighted-additive and reference-dependent models. Issue 1 (16th March 2015) - Sahay, Arvind; Mukherjee, Sumitava; Dewani, Prem Prakash
Abstract : Purpose: – The purpose of this paper is to study how consumers process price frames of product bundles (product plus surcharge) and discount offers to weigh contentious positions between the weighted-additive and the reference-dependent models. Further, some research suggests bundling, while others suggest partitioning to be a more effective pricing strategy. This research evaluated the relative influences of different price frames to examine which model is supported and what are the boundary conditions for price framing. Design/methodology/approach: – Two online studies were conducted on Indian adults who had prior experiences of online purchases. They were asked to judge attractiveness of bundles (product along with shipping surcharge). Discounts were shown on the product, the surcharge or on the overall bundle either as partitioned prices or as a bundle. Findings: – Across two studies on low- and high-priced products, discounts on shipping surcharge increased attractiveness of the bundle compared to a similar discount on the product or on the overall bundle, supporting the reference-dependent model. Further, for a low-priced product, bundling increased attractiveness, while for a high-priced product, partitioning was more attractive. Research limitations/implications: – More research is needed to examine whether these results translate to other kinds of products, surcharges or discount promotions and in different populations. Originality/value: – This research makes important contributions to theoretical and practical aspects of bundling and partitioned pricing research. It also adds much needed data about evaluation of product bundles with shipping surcharges among Indian customers.